Artificial Wombs, Thomson and Abortion – What Might Change? - Pruski, Michal; Playford, Richard C. (Diametros, 2022)
Ectogenesis (artificial wombs) might soon become a reality. This paper will analyse how the development of such technologies will affect Judith Jarvis Thomson’s defence of abortion, and what the potential consequences of this will be for society. Thomson attempts to justify abortion by appealing to the mother’s right to bodily autonomy. We will argue that once these technologies have been developed, the right to abortion can no longer be justified by such appeals. As a result, when justifying abortion, Thomson-style arguments will no longer work, and a very different strategy will have to be adopted by those wishing to justify its permissibility. Anticipating a consequent weaker position of the pro-choice view, we briefly consider some of the practical implications of ectogenesis for society: effects on parental dynamics, governmental expenditure, research, and gender equality.